Penguatan Modal Sosial Dalam Pengembangan Pertanian Organik (Studi Kasus Pada Kelompok Tani Mulyo 1 Desa Gentungan Kecamatan Mojogedang Kabupaten Karanganyar) - Astari, Astin Riski; Winarno, Joko; Sugihardjo, Sugihardjo (Universitas Muhammadiyah Semarang, 2024)
Strengthening social capital in the development of organic farming is very important because organic farming often involves farming communities working together to achieve common goals. The Mulyo 1 Farmers Group is indeed one of the farmer groups that has succeeded in implementing organic farming, but until now there are still problems in developing organic farming. There are concerns about organic farming activities in the Mulyo 1 Farmers Group because some farmers, especially the elderly, are currently unable to make organic fertilizer alone. This study uses a qualitative method. There were 10 informants in the research, some of whom were determined purposively, then the rest were selected by snowballing. Data analysis was carried out by triangulating sources and methods. The results of the research show that (1) the elements of social capital in the Mulyo 1 Farmers Group include, (a) trust which is maintained by honesty and openness, (b) the norms of the Mulyo 1 Farmers Group are harmony and tolerance, mutual respect, and being fair, (c) the network in the Mulyo 1 Farmers Group was formed through cooperation and communication. The obstacles to the Mulyo 1 Farmers Group in developing organic farming are the old age of the farmer group members and the lack of initiative of the farmer group members.